Three‐dimensional (3D) geometric morphometric analysis of human premolars to assess sexual dimorphism and biological ancestry in Australian populations. Issue 2 (15th February 2018) - Yong, Robin; Ranjitkar, Sarbin; Lekkas, Dimitra; Halazonetis, Demetrios; Evans, Alistair; Brook, Alan; Townsend, Grant
Abstract: Objectives: This study aimed to investigate size and shape variation of human premolars between Indigenous Australians and Australians of European ancestry, and to assess whether sex and ancestry could be differentiated between these groups using 3D geometric morphometrics. Materials and Methods: Seventy dental casts from each group, equally subdivided by sex, were scanned using a structured‐light scanner. The 3D meshes of upper and lower premolars were processed using geometric morphometric methods. Seventy‐two landmarks were recorded for upper premolars and 50 landmarks for lower premolars. For each tooth type, two‐way ANOVA was used to assess group differences in centroid size. Shape variations were explored using principal component analysis and visualized using 3D morphing. Two‐way Procrustes ANOVA was applied to test group differences for ancestry and sex, and a "leave‐one‐out" discriminant function was applied to assess group assignment. Results: Centroid size and shape did not display significant difference between the sexes. Centroid size was larger in Indigenous Australians for upper premolars and lower second premolars compared to the Australians of European ancestry. Significant shape variation was noted between the two ancestral groups for upper premolars and the lower first premolar. Correct group assignment of individual teeth to their ancestral groups ranged between 80.0 and 92.8% for upper premolars and 60.0 and 75.7% for lower premolars. Discussion: Our findings provide evidence of significant size and shape variation in human premolars between the two ancestral groups. High classification rates based on shape analysis of upper premolars highlight potential application of geometric morphometrics in anthropological, bioarcheological and forensic contexts.